Migración sur-sur: factores relacionales e inserción segmentada de la población boliviana y peruana en la ciudad de Córdoba, Argentina - Bologna, Eduardo León; Falcón, María del Carmen (El Colegio de México A.C., 2016)
Populations of Bolivian and Peruvian origin resident in the city of Córdoba are analyzed as a case of south-south migration, the main hypothesis with the greatest explanatory weight being relational factors regarding the differences in development between the regions of origin and destination.The authors compare the demographic structure, educational integration and spatial distribution of the two populations between the national censuses of 2001 and 2010. For reasons of data availability, occupational insertion is only described in the 2001 census, and through records in the surveys for the following period.The authors conclude that Córdoba’s attraction is due more to the historical links these two migrant groups have forged with the city than to its level of economic or social development.